Magnetic Resonance Vessel Wall Imaging in Central Nervous System Vasculitides: A Case Series. Issue 6 (November 2020) - Padrick, Matthew M.; Maya, Marcel M.; Fan, Zhaoyang; Szumski, Nicholas; Lyden, Patrick D.; Song, Shlee S.; Dumitrascu, Oana M.
Abstract : Introduction: We aim to report 3 cases of central nervous system (CNS) vasculitides, in which high-resolution magnetic resonance vessel wall imaging (HR-VWI) findings were instrumental in the diagnosis and management. Case Report: Case 1: A 41-year-old obese, smoker female with arterial hypertension presented with recurrent transient ischemic attacks. Computed topography angiography demonstrated bilateral middle cerebral artery (MCA) stenosis. HR-VWI revealed uniform enhancement and thickening of the arterial wall, suggestive of MCA vasculitis. The patient reported chronic calf rash that was biopsied and revealed unspecified connective tissue disease. With immunomodulation, patient remained asymptomatic and 6-month surveillance HR-VWI showed improved MCA stenoses. Case 2: A 56-year-old male with herpes simplex virus 1 encephalitis was treated with antiviral therapy and improved clinically. Two months later, the brain magnetic resonance imaging revealed new temporo-parietal edema and distal MCA hyperintense vessels. HR-VWI showed MCA concentric smooth contrast enhancement, that was attributed to postinfectious vasculitis and had resolved on follow-up HR-VWI. Case 3: A 41-year-old male presented with 1-week of headache and encephalopathy. Brain magnetic resonance imaging revealed punctate multifocal acute ischemic infarcts and no contrast-enhancement. HR-VWI showed multifocal diffuse enhancement of distal cerebral vasculature. Patient subsequently developed branch retinal artery occlusion and hearing loss and was diagnosed with Susac syndrome. No recurrent symptoms were noted after immunotherapy initiation. Conclusions: In these 3 cases, HR-VWI identified distinctive vascular inflammatory changes, which were crucial to guide the etiological workup, positive diagnosis, surveillance neuroimaging, and targeted treatment. HR-VWI is an important diagnostic tool in CNS vasculitides, by providing nuanced information about arterial wall integrity and pathology.